Meraih Hidup Bermakna: Logoterapi untuk Menurunkan Depresi pada Perempuan Korban KDRT - Qurrota A’yuni Fitriana; M. Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Women victims of domestic violence experience both physical and psychologicaltrauma that may contribute in the emergence of depression symptoms. Depression is acondition when individu losing their meaning of life. The intervention for makingmeaningful life discovered by Viktor Frankl that named logotherapy. The purpose of thisstudy is to investigate the effectiveness of logotherapy in reducing depression for womenvictims of domestic violence. One-group pretest-posttest design by using a double pretestwas applied. Beck Depression Inventory II (BDI-II) and meaning in life scale asmanipulation check was used. The participants of this study are 6 womens. Logotherapywas administered for 6 sessions in 3 weeks. The result of this study are similar with thehypothesis showed where logotherapy significantly decreased depression in women victimsof domestic violence (F (r) = 9.333, p = .000). This study used logotherapy group, whereasamong participants have a chance to share their feelings and mutual enforcing formeaningful life.